90Sr/137Cs ratios in soil of epicentral zones of «Experimental Field» testing site of Semipalatinsk Test Site. (March 2020) - Baklanova, Yu.V.; Umarov, M.A.; Dyuisembaeva, M.T.; Lukashenko, S.N.
Abstract: The paper presents the results of 90 Sr/ 137 Cs isotopic ratios in the soil surface layer in the venues of surface and atmospheric nuclear tests at the territory of the «Experimental Field » site of the Semipalatinsk Test Site. One of the main factors in the radiation impact of a nuclear explosion on the environment is the decay of fission products. The determination of 137 Cs activity in soil is carried out by accurate, rapid and sufficiently cheap gamma-spectrometric method, while the existing methods of determining 90 Sr activity are quite problematic: they either have sufficiently high detection limits or are time-consuming. As an alternative method, 90 Sr activity can be determined using its correlation dependence with 137 Cs activity. According to the literature, each test has its own fission product ratio, depending on the nuclear charge. As a result of the conducted research it was revealed that one epicenter is located at the technical site P-1, the ratio of 90 Sr/ 137 Cs is equal to 4, 8; at the technical site P-3 - 2 epicenters, the ratio of 90 Sr/ 137 Cs is equal to 0, 8 and 0, 9; at the technical site P-5 - 6 epicenters, the ratio of 90 Sr/ 137 Cs is in the range of 0, 9-2, 1; at the technical sites P-2, P-7 - 19 epicenters, the ratio of 90 Sr/ 137 Cs is in the range of 0, 6-2, 1. It is assumed that the differences in the value of fission product ratios are due to different types and capacities of nuclear charges, as well as different explosion altitudes. The obtained ratios allow to calculate 90 Sr by 137 Cs activity in soil of the epicentral zones at the territory of the «Experimental Field » testing site by the computational method.